Assessment of Substantial Liver Fibrosis by Real‐time Shear Wave Elastography in Methotrexate‐Treated Patients With Rheumatoid Arthritis. (12th August 2015) - Kim, Tae Yeob; Kim, Ji Yeoun; Sohn, Joo Hyun; Lee, Hye-Soon; Bang, So-Young; Kim, Yongsoo; Kim, Min Yeong; Jeong, Woo Kyoung
Abstract : Objectives: A concern about methotrexate (MTX)‐related liver fibrosis in patients with rheumatoid arthritis (RA) is still unresolved. This study investigated the correlation between liver stiffness and the cumulative MTX dose and the risk factors associated with substantial liver fibrosis assessed by real‐time shear wave elastography (SWE), a recently introduced technique to evaluate liver stiffness in patients with RA. Methods: Data from 185 patients with RA were prospectively collected. Patients were divided into 3 groups according to cumulative MTX dose (group 1, total dose <1500 mg; group 2, 1500–4000 mg, and group 3, >4000 mg) and compared with healthy control participants. A Pearson correlation analysis was performed to evaluate correlations between liver stiffness and other clinical and laboratory variables. Substantial liver fibrosis was defined as liver stiffness of greater than 8.6 kPa by SWE. Associated factors were tested in a multivariate logistic analysis. Results: The mean liver stiffness value in healthy controls was significantly lower than in patients with RA treated with MTX ( P < .006), but there was no significant difference among the MTX groups. Liver stiffness and the cumulative MTX dose was not correlated. Substantial liver fibrosis was detected only in 9 patients (4.9%). Multivariate analysis adjusted by age and sex revealed that only a high body mass index (odds ratio, 1.79; 95% confidence interval, 1.34–2.39; P < .001) was associated with liver stiffness of greater than 8.6 kPa. Conclusions: Substantial liver fibrosis on SWE was observed in about 5% of MTX‐treated patients with RA and was associated with only a high body mass index but not with the cumulative MTX dose, suggesting that other comorbidities might have a more important role in liver fibrosis.